Nosocomial infections within the first month of solid organ transplantation. Issue 2 (24th March 2014) - Dorschner, P.; McElroy, L. M.; Ison, M.G.
Abstract Infections remain a common complication of solid organ transplantation. Early postoperative infections remain a significant cause of morbidity and mortality in solid organ transplant (SOT) recipients. Although significant effort has been made to understand the epidemiology and risk factors for early nosocomial infections in other surgical populations, data in SOT recipients are limited. A literature review was performed to summarize the current understanding of pneumonia, urinary tract infection, surgical‐site infection, bloodstream infection, and Clostridium difficult colitis, occurring within the first 30 days after transplantation.